Vitamin A rich banana adoption in Cibitoke and Gitega, Burundi- a field diagnostic study - Ocimati, Walter; Bizoza, Saidi; Nduwimana, Innocent; Iradukunda, Francois; Blomme, Guy; Ekesa, Beatrice (2022)
Vitamin A deﬁciency (VAD) is a widespread problem in the sub-Saharan Africa (SSA). Here the population is predominantly reliant plant-based diets. Thus, identification of popular food sources with higher vitamin A contents is a suitable means for addressing VAD. For example, Burundi has a VAD prevalence of 46%. In this region, bananas and plantains are a cheap staple food crop and therefore, offer a good avenue for supplying vitamin A in the diets. To address VAD in the region, Bioversity International under through Consortium for Improving Agriculture-based Livelihoods in Central Africa (CIALCA) and HarvestPlus grants undertook studies to fast-track deployment of native and introduced pro-vitamin A rich bananas. Through the OneCGIAR - TAFS WCA and CIALCA bridge year funds, the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) undertook an adoption study of the VABs in the pilot sites in Burundi to inform plans for a wider scaling effort. The study interviewed 332 household heads, had qualitative discussions in four focus groups. A positive perception was observed among farmers growing the VABs due to their early maturity, high vitamin A content, and long storage life. Adoption rates among initial beneficiaries were 45% in Gitega and 12% in Cibitoke. These rates could have been higher if not for the impact of COVID-19 that interrupted project activities and prevented additional support to the farmers, just after accessing the plantlets. For example, some farmers were skeptical of the small macro-propagated plantlets as they were used to using suckers, and as such failed to plant them. Some lost plants due to the dry spell, yet simple practices such as mulching could have sustained the plants. In Cibitoke, the government policy assigning the region to rice production led to uprooting and abandonment of banana by most households, including those in the pilot area, leading to the low adoption. However, willingness to adopt these materials was high, varying between 86-90% across the sites. The adopters were observed to have expanded the area under the VAB. Diffusion from the adopters to other farmers was also high, with two farmers reporting to have shared over 200 suckers with over 70 farmers in Gitega. Alternative uses including beer making had been identified by farmers at the time of the study. Access to planting materials and awareness on the nutritional value of the VABs, especially among indirect beneficiaries, were a major stumbling block to VAB adoption, expansion, and use. Thus, scaling efforts will need to focus on establishing robust seed systems and enhancing community awareness on the importance of vitamin A in their diets. Some farmers were observed to have a large influence on the dissemination of planting materials, thus, could be targeted as conduits in a more sustainable and robust seed system. Ongoing efforts to co-invest with partners such as ENABEL, World Vision, and the NARS will be handy in furthering the adoption and use of these varieties.